2021
DOI: 10.3389/fcosc.2021.726991
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence for Whom?

Abstract: This perspective essay considers ethical and conceptual questions around who coexistence is for, who it affects, and who is to make it happen. The introduction considers some approaches to thinking about human-wildlife coexistence, debates on the utility of the concept and reasons for its current emergence into the mainstream. It next outlines the preliminary conception of coexistence informing this essay. The discussion considers challenges for a narrow conservation-oriented framing of human-wildlife coexiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…We seek to understand coexistence dynamically and holistically, including positive aspects of human-wildlife relationships, alongside the more widely publicized negative interactions such as crop damage, livestock depredations, attacks on humans, and retaliatory killing (Pooley, 2021). We therefore accept coexistence as "a state where conflict exists but where interactions are kept within acceptable limits" (Linnell, 2013, p. 26).…”
Section: What Do We Mean By Coexistence?mentioning
confidence: 99%
See 1 more Smart Citation
“…We seek to understand coexistence dynamically and holistically, including positive aspects of human-wildlife relationships, alongside the more widely publicized negative interactions such as crop damage, livestock depredations, attacks on humans, and retaliatory killing (Pooley, 2021). We therefore accept coexistence as "a state where conflict exists but where interactions are kept within acceptable limits" (Linnell, 2013, p. 26).…”
Section: What Do We Mean By Coexistence?mentioning
confidence: 99%
“…Approaches that build on such deep cultural relationships with large carnivores can play fundamental roles in promoting the value of carnivores as a social as well as a natural resource (Nijhawan and Mihu, 2020). These examples contribute to an understanding of coexistence as complex, multi-layered and deeply rooted in culture, and demonstrate the importance of viewing coexistence through different perspectives and cultural lenses (Adams and Mulligan, 2003;Peterson et al, 2010;Pooley, 2021).…”
Section: What Do We Mean By Coexistence?mentioning
confidence: 99%
“…All the difficulties named as key to achieve success in the reintroduction projects are hard to solve without changing paradigms. To restore biodiversity, it is essential to seek new ways of thinking and doing conservation, adding the coexistence perspective, where interactions between people and wildlife are managed to keep wild species population sharing space and resources with human communities in a socially fair way (Pascual et al, 2021;Pooley, 2021;Pooley et al, 2021).…”
Section: Actions Using a Human Dimensions Approach And The Lack Of Detailmentioning
confidence: 99%
“…As HEC is actually a conflict between people about the management of elephants and the use resources, the political economy and social dimensions need to be taken more into the focus of HEC analysis and management to move towards coexistence between elephants and people [42,43]. The great challenge conservation institutions face when targeting HEC management is the high complexity and dynamics within the socio-ecologic systems involved [44][45][46][47]. This complexity calls for a transdisciplinary approach, which may exceed single institutions' capacities [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific debate around HEC/HWC and coexistence has shown that these powerful terms may have varying definitions and evoke various reactions and emotions [45,65]. Whether we define the journey from conflict to coexistence as a continuum [66] or recognize lack of clear delineation [54] or the need to introduce a new term and concept [67], the call to change the state of conflict to something more beneficial and more equitable for those living with it is generally supported in theory [56,68].…”
Section: Introductionmentioning
confidence: 99%